Data on impact of soil compaction, drought and their combination on vertical root distribution, morphological traits, and soil water patterns in Urochloa hybrids - Cardoso Arango, Juan Andres; Mayorga Cobos, Mildred Julieth (2024)
Urochloa grasses are typically grown in rain-fed systems, where soil compaction and water limitation (drought) significantly reduce their productivity. Deep roots are a key trait in these grasses, allowing them to access water from soil layers at depth during droughts, which helps to prevent water stress (Cardoso et al., 2015). However, soil compaction may limit the ability of roots to penetrate deeply, restricting water uptake and increasing vulnerability to drought. This dataset describes the impact of four soil conditions (control, compaction, drought, and a combination of compaction and drought) on five Urochloa hybrids grown under greenhouse conditions. It includes measurements of root dry mass distribution at 10 cm intervals down a 100 cm soil column, D95 (the depth at which 95% of root mass is concentrated), root morphological traits (number, diameter, and porosity), and shoot dry mass. The data includes information on volumetric water content throughout the soil profile. Such data is not available for Urochloa hybrids or other tropical grasses, making it a valuable tool for understanding their stress responses, water uptake and guiding breeding efforts for more resilient varieties. The data can be used in plant ideotyping and functional structural modelling of roots under various soil conditions to support the development and breeding of more resilient Urochloa hybrids to edapho-climatic stresses such as soil compaction, drought and the combination of both.